Karakteristik Kimia dan Mikrobiologi Frozen Yoghurt: Substitusi Bakteri Asam Laktat dengan Penambahan Sari Buah Stroberi (Fragaria ananassa L) sebagai Pangan Probiotik - Refi, Okta Refi Anggraini; Jannah, Hidayatul; Febrianti, Fristhy; Ramadhanti, Nurazizah; Fatdillah, Haezah; Alzahra, Huriya; Pratama, Yudha Endra (CV. SINAR HOWUHOWU, 2026)
Probiotics are live microorganisms that are good for consumption because they have health benefits. To improve the quality of probiotic food products, fruit juice can be added. This study aims to examine the substitution of Lactobacillus fermentum and Lactiplantibacillus plantarum as starters, as well as the addition of strawberry juice (Fragaria ananassa L) on the pH value, total titratable acidity (TTA), and total lactic acid bacteria in frozen yogurt. The method used in this study is a 3x3 factorial Randomized Block Design (RBD) with 3 replications. The treatments conducted in this study were the addition of starter at 4%, 5%, and 6%, and the addition of strawberry juice at 0%, 12.5%, and 25%. Based on the research results, a significant effect (P<0.05) was observed with the addition of 6% starter on pH value (4.51), total titratable acidity (1.54), and total lactic acid bacteria (678x10^8 CFU/gr). The addition of 25% strawberry juice had a significant effect (P<0.05) on pH value (4.47), total titratable acidity (1.52), and total lactic acid bacteria (459x10^8 CFU/gr). Based on the research results, it can be concluded that the best results in yogurt production based on pH value, total titratable acidity (TTA), and total lactic acid bacteria were achieved with the addition of 6% starter and 25% strawberry juice.